Overview of caustic ingestion cases at the Children’s Hospital of Vilnius University Hospital Santaros klinikos between 2011 and 2018 - Narkutė, Airida; Žilinskaitė, Virginija (Acta medica Lituanica, 2020)
Background. Although not common, caustic ingestion can cause serious injury and sequelae. Clinical symptoms do not always represent the depth of lesions of the intestinal tract, which makes management of these patients difficult. Materials and methods. Between 2011 and 2018, we performed a retrospective one-centre study on ingestion of corrosive agents by children. We used ICD-10 codes of X49, X54.X, and T28.2. Cases of eye or skin burns were excluded. Results. Sixty-five cases were found. Due to a lack of data, we analysed 56 cases. The majority of them were boys (64%); 41% of patients were between 12 and 24 months old. The median age was one year. In 68% of cases, the corrosive substance was alkali: laundry detergent pods and sodium hydroxide accounting for 25% and 14%, respectively. Of the hospitalised patients and all those admitted to the paediatric intensive care unit (PICU), 78% had oesophagogastroduodenoscopy (EGD), 61% within 24 h after ingestion. The time of EGD was not known for 29% of patients. Nine (29%) had 2nd- or 3rd-degree burns of the oesophagus or the stomach, one of them did not have any visible changes of the lips and oral mucosa or any symptoms. Conclusions. Physicians should be suspicious about potential lesions of the gastrointestinal tract when managing caustic ingestion cases. It is recommended to perform EGD for symptomatic children within 24 hours after the accident.
Keywords: caustic ingestion; corrosive substance; alkali; acid; endoscopy